Effect of pre-operative communication using anaesthesia information sheet on pre-operative anxiety of patients undergoing elective surgery—A randomised controlled study - Utpala Kharod; Nirali N Panchal; Jagdish Varma; Krupa Sutaria (Indian Journal of Anaesthesia, 2022)
Background and Aims: Pre-operative anxiety can affect psychological and physiological parameters during the intra-operative period. Pharmacological measures used to reduce pre-operative anxiety have their associated adverse effects. Pre-operative anaesthesia education is one of the non-pharmacological tools to reduce anxiety, but very limited literature is available in the Indian scenario. Hence, this study was designed to evaluate the effect of pre-operative counselling of patients using anaesthesia information sheet on pre-operative anxiety of patients who underwent elective surgery as the primary outcome. Secondary objectives were to assess the pre-operative anxiety for surgery, correlation of demographic data with pre-operative anxiety, and the common causes responsible for pre-operative anxiety. Methods: Total 110 patients were randomly allocated into two groups. Group-A was counselled using anaesthesia information sheet and in Group-B, conventional counselling was done during pre-anaesthesia check-up. Anxiety scores for anaesthesia and surgery were measured using visual analogue scale for anxiety (VAS-A). VAS-A score was compared pre- and post-intervention.Effect of intervention was assessed by comparing reduction in VAS-A score in both groups with paired t-test. Data were analysed using STATA (14.2) version. Results: The mean reduction in VAS-A for anaesthesia was more in Group-A compared to Group-B (16.6 ± 6.9 vs. 4.4 ± 5.8; P < 0.001). The mean reduction in VAS-A for surgery was more in Group- A compared to Group- B (14.6 ± 7.8 vs. 4.8 ± 7.3; P < 0.001). Conclusion: Pre-operative counselling using anaesthesia information sheet is helpful in reducing pre-operative anxiety more efficiently. Further trials are required to assess transferability in other settings.